Efficacy of annealing and fabrication parameters on photo-response of SiGe in TiO2 matrix. (24th June 2019) - Sultan, M T; Gudmundsson, J T; Manolescu, A; Teodorescu, V S; Ciurea, M L; Svavarsson, H G
Abstract: SiGe nanoparticles dispersed in a dielectric matrix exhibit properties different from those of bulk and have shown great potential in devices for application in advanced optoelectronics. Annealing is a common fabrication step used to increase crystallinity and to form nanoparticles in such a system. A frequent downside of such annealing treatment is the formation of insulating SiO2 layer at the matrix/SiGe interface, degrading the optical properties of the structure. An annealing process that could bypass this downside would therefore be of great interest. In this work, a short-time furnace annealing of a SiGe/TiO2 system is applied to obtain SiGe nanoparticles without formation of the undesired SiO2 layer between the dielectric matrix (TiO2 ) and SiGe. The structures were prepared by depositing alternate layers of TiO2 and SiGe films, using direct-current magnetron sputtering technique. A wide range spectral response with a response-threshold up to ∼1300 nm was obtained, accompanied with an increase in photo-response of more than two-orders of magnitude. Scanning electron microscopy, transmission electron microscopy, energy-dispersive x-ray spectroscopy and grazing incidence x-ray diffraction were used to analyze the morphological changes in respective structures. Photoconductive properties were studied by measuring photocurrent spectra using applied dc-voltages at various temperatures.